Pengembangan Bahan Ajar Matematika Berbasis Budaya Lokal Masyarakat Cirebon - Mahpudin; Yuyu Yuliati (LPPM Universitas Buana Perjungan Karawang, 2019)
In accordance with the level of his age, learning mathematics in elementary schools should start from a concrete concept first before students are brought to the concept in the form of abstract mathematical symbols. Local culture of the community becomes a real part that is faced by students in their daily lives. So the use of local culture as a mathematics learning content can lead students to a concrete mathematics learning experience. This paper tries to explain the results of research focusing on the development of local culture-based mathematics teaching materials in the Cirebon community. The purpose of this study was to produce mathematics materials based on the local culture of Cirebon society. Teaching material developed meets valid and effective criteria. the type of research used is development research with ADDIE (Analysis, Design, Development, Implementation, Evaluation) procedures. The results of this study indicate an increase in students' mathematical understanding after learning is applied by using local culture-based mathematics teaching materials in the Cirebon community. The increase in the average value of students 'mathematical understanding abilities is from 41 to 71. Thus, the use of local culture-based mathematics teaching materials in Cirebon society can improve students' mathematical understanding abilities.